2015
DOI: 10.1097/mbc.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2C9 and VKORC1 genetic polymorphisms upon warfarin dose requirements in Egyptian patients with acute coronary syndrome

Abstract: Warfarin is the most widely prescribed anticoagulant drugs. Cytochrome P450-2C9 (CYP2C9) and vitamin K epoxide reductase-oxidaxe complex subunit 1 (VKORC1) contribute significantly to the variability of warfarin dose requirements among patients. We investigated the impact of CYP2C9 and VKORC1 polymorphisms on the variability of warfarin dosage requirements in Egyptian patients with acute coronary syndrome and their association with other nongenetic factors. Eighty participants with acute coronary syndrome were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, the study by Alrashid et al [38] was considered of poor quality as there was no reporting of the r 2 value for the dosing model. The sample-size used in some of the studies was less than 100, which is relatively low and may have affected the power of their conclusions [31, 32, 34, 39]. Testing for the Hardy-Weinberg equilibrium was reported in all studies except those by Yildirim et al [44] and Ghozlan et al [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study by Alrashid et al [38] was considered of poor quality as there was no reporting of the r 2 value for the dosing model. The sample-size used in some of the studies was less than 100, which is relatively low and may have affected the power of their conclusions [31, 32, 34, 39]. Testing for the Hardy-Weinberg equilibrium was reported in all studies except those by Yildirim et al [44] and Ghozlan et al [32].…”
Section: Resultsmentioning
confidence: 99%
“…al. [32]. Such discrepancy could be in part due to the small sample sizes used in the different studies concerning the Egyptian population, in particular the studies by Ghozlan, Ekladious, and Bazan and their colleagues [31, 32, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have demonstrated that there is a strong association between CYP2C9 variant alleles and warfarin dose requirement . After that, many studies have certified the significant effect of CYP2C9 on warfarin doses in adult patients . Moreover, a dosing algorithm for adult patients has been established by the US Food and Drug Administration and International Warfarin Pharmacogenetics Consortium .…”
Section: Introductionmentioning
confidence: 99%
“…The estimated regression equation was able to account for 20.5% of the overall variability in warfarin maintenance dose. Similarly, Ghozlan et al [24] reported that genetic polymorphisms in VKORC1, CYP2C9 along with age and height were determinants of warfarin dose requirements in Egyptian population with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%